The Results of Fiduciary Law Warranties which the Objects are Transferred to Third Parties - Nabila Ananda Putri; Siti Malikhatun Badriah (Universitas Islam Sultan Agung, 2023)
This study aims to find out and analyze legal protection for fiduciary guarantee holders whose objects are transferred to third parties and legal protection for fiduciary guarantee holders transferred to third parties in decisions Number: 45 / Pdt.Eks / 2015 / PN.Smg. the results of this study, it is known that Legal protection for Fiduciary Guarantees Transferred to Third Parties, if the object of fiduciary collateral turns out to be transferred to a third party or transferred without the creditor's knowledge, while the debtor and third parties acknowledge it, then the creditor can give summons which subsequently have the force to withdraw objects guaranteed can In Decision Number 45 / Pdt.Eks / 2015 / PN.SMG, against debtors whose objects of fiduciary collateral are not registered forcibly executed by creditors, the debtor can file a lawsuit made by creditors to the court based on the provisions of the Civil Code for violating the provisions of UUJF.